2021
DOI: 10.1093/ajcp/aqab009
|View full text |Cite
|
Sign up to set email alerts
|

Liver Pathology and SARS-CoV-2 Detection in Formalin-Fixed Tissue of Patients With COVID-19

Abstract: Objectives The novel coronavirus, severe acute respiratory syndrome coronavirus 2, causing coronavirus disease 2019 (COVID-19) remains a global health threat and a significant source of human morbidity and mortality. While the virus primarily induces lung injury, it also has been reported to cause hepatic sequelae. Methods We aimed to detect the virus in formalin-fixed tissue blocks and document the liver injury patterns in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…A number of studies have examined the histopathological effects of COVID‐19 on the respiratory tract, but few have specifically examined the impact on the liver, ( 9 , 10 ) in part because of limited tissue availability. Much of the existing literature is based on reports of small case series, ( 11 , 12 ) although a few larger case series have been published as well.…”
mentioning
confidence: 99%
“…A number of studies have examined the histopathological effects of COVID‐19 on the respiratory tract, but few have specifically examined the impact on the liver, ( 9 , 10 ) in part because of limited tissue availability. Much of the existing literature is based on reports of small case series, ( 11 , 12 ) although a few larger case series have been published as well.…”
mentioning
confidence: 99%
“…Liver disease is a well-documented and common problem in severe COVID-19 [5] , [6] , [7] , [8] . Pathologic changes in the liver ascribed to SARS-CoV2 include portal tract/lobular inflammation, microvascular thrombi, and hepatocyte necrosis [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Liver disease is a well-documented and common problem in severe COVID-19 [5] , [6] , [7] , [8] . Pathologic changes in the liver ascribed to SARS-CoV2 include portal tract/lobular inflammation, microvascular thrombi, and hepatocyte necrosis [6] , [7] , [8] . However, several studies have indicated that SARS-CoV2 RNA is either not detectable or present in a minority of COVID-19 related hepatitis cases [6] , [8] , [9] though abundant in the lung [9] , [10] , [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 and TMPRSS2, the 2 major viral cell entry factors, are expressed at only low levels in hepatocytes and non-parenchymal cells. 3,5 Even though SARS-CoV2 RNA has been detected in the livers of COVID-19 patients, 6 functional studies demonstrating robust SARS-CoV2 infection of liver cells are pending. 3 Histopathological studies of COVID-19 livers reported an increased prevalence of moderate steatosis, mild lobular and portal inflammation, and sinusoidal thrombosis.…”
mentioning
confidence: 99%
“…ACE2 and TMPRSS2, the two major viral cell entry factors, are expressed at only low levels in hepatocytes and non-parenchymal cells [ 3 , 5 ]. Even though SARS-CoV2 RNA has been detected in the livers of COVID-19 patients [ 6 ], functional studies demonstrating robust SARS-CoV2 infection of liver cells are pending [ 3 ].…”
mentioning
confidence: 99%